Whole blood transcriptome analysis of lactating Murrah buffaloes divergent to contrasting genetic merits for milk yield - Sikka, Poonam; Singh, Kunwar Pal; Singh, Inderjeet; Mishra, Dwijesh Chandra; Paul, Shyam Sundar; Balhara, Ashok K.; Andonissamy, Jerome; Chaturvedi, Krishna Kumar; Rao, Atmakuri Ramakrishna; Rai, Anil (Frontiers in Animal Science, 2023)
Functional genome profiling of Murrah buffaloes (Bubalus bubalis) was performed for milk-production trait by whole blood transcriptome analysis comparing RNA-seq data assembled from high and low milk producing multiparous (5 -6 parity) animals. These buffaloes reflected the genetic merit inherited as daughters born to extremely high- and low-end bulls evaluated under a progeny testing scheme and ranked by the estimated breeding value. The average standard milk yield (SMY) over the 305 d during the parity was recorded as 2909.50L ± 492.63 and 1869.57 ± 189.36L in high- and low-performance buffaloes, respectively. The “reference” assembly data was assembled from transcriptome libraries of a group of buffaloes (n=16), comprising of animals in different physiological states. Replicates selected within each category of the high and low genetic merit animals showed a correlation coefficient of high order (R2=0.98) while comparing with the `reference' assembly. The sequence data of selected buffaloes, mapped over the Mediterranean water buffalo genome, revealed differentially expressed genes (DEGs) distinctly depicted via heat maps and volcano plots obtained for two categories of animals, determining more than 25,000 genes via the Cufflink analysis. DEGs included 83 down-regulating and 142 up-regulating genes (p<0.05, FDR<0.05). Functional classification of the DEGs revealed a fine networking of biological processes, primarily cell signaling, cell proliferation, cell differentiation, RNA splicing, fat metabolism, and inflammasome generation. These processes are regulated by transcription factors and binding proteins covered under the network of TNF alpha signaling, NF-kappa B signaling and MAPK PI3K-AKT signaling pathways/ cascade emerged as main biological pathways. Emerged pathways revealed remarkably intricate tuning of metabolic and cell development processes converging into milk production in buffaloes. Segregated patterns of gene expression obtained for high and low milk producing buffaloes using the non-invasive method of whole blood transcriptome analysis has emerged as a promising resource comprising gene network and protein -protein interactions, primarily involved in lactation. Synergism of transcription factors and binding proteins promoting epigenetic regulation at all development stages of mammary tissue induce mammogenic and lactogenic responses for subsequent milk secretion under optimum feeding management. These findings may help improve breeding strategies to achieve the desired milk yield in Murrah buffaloes.